The effect of social support on home isolation anxiety and depression among college students in the post-pandemic era: the mediating effect of perceived loss of control and the moderating role of family socioeconomic status - Shi, Hui (Frontiers in Public Health, 2024)
Background There is an escalating concern about the rising levels of anxiety and depression among college students, especially during the post-pandemic era. A thorough examination of the various dimensions of social support and their impact on these negative emotions in college students is imperative. Aim This study aimed to determine if a perceived loss of control mediates the relationship between social support and levels of anxiety and depression among college students during the post-pandemic era. Additionally, it examined whether family socioeconomic status moderates this mediated relationship. Methods We administered an online cross-sectional survey in China, securing responses from 502 participants. The sample comprised home-isolated college students impacted by COVID-19. Established scales were employed to assess social support, anxiety, depression, perceived loss of control, and family socioeconomic status. Analytical techniques included descriptive statistics, correlation analysis, and a bootstrap method to investigate mediating and moderating effects. Results Social support was found to negatively affect anxiety and depression in college students, with perceived loss of control partially mediating this relationship. In addition, family socio-economic status was shown to moderate this moderating process. Furthermore, family socioeconomic status influenced this mediation, with higher socioeconomic families exhibiting a stronger moderating effect on perceived loss of control across different dimensions of social support. Conclusion This study may help to develop strategies to mitigate the impact of anxiety and depression in the lives and studies of university students during unexpected public health crises, and to promote better mental health among college students.